Peripheral blood concentration of toll-like receptor-4 and its accuracy for prediction of postpartum performances of transition zebu (Bos indicus) cows - MANIMARAN, AYYASAMY; WANKHADE, PRATIK RAMESH; KUMARESAN, ARUMUGAM; PATBANDHA, TAPAS K; SIVARAM, MUNIANDY; JEYAKUMAR, SAKTHIVEL; RAJENDRAN, DURAISAMY (The Indian Journal of Animal Sciences, 2021)
In this study, we evaluated the peripheral concentrations of Toll-like receptors (TLR)-4 during transition period in relation to postpartum productive and reproductive performances of Deoni (zebu) cattle. Accuracy and threshold values of TLR-4 to predict the postpartum performance, were also estimated using receiver operating characteristics (ROC) analysis. Blood samples were collected at weekly intervals during transition period (from 21 days before to 21 days after calving) and TLR-4 concentration was estimated using bovine specific ELISA kits. Plasma TLR-4 concentration was significantly higher on third day of postpartum in cows that became pregnant within breeding period than the cows that remained non-pregnant (4.48 vs 1.80 ng/mL). ROC analysis revealed that the accuracy of TLR-4 for predication of ability to become pregnant within breeding period was acceptable (AUC: 0.75) with a threshold value of 2.13 ng/mL. It is concluded that concentrations of TLR-4, during transition period, could be used for predicting the possibilities of Deoni cows getting pregnant within the breeding period with moderate accuracy.